The development of Malay entrepreneurship in Malaysia - Syahira Hamidon (Kuala Lumpur : Institut Terjemahan dan Buku Malaysia, 2014)
This book on the development of entrepreneurship among the majority race in Malaysia, the Malays, is based on research conducted for a Phd thesis and examines the successes, problems, shortcomings and impacts of a public policy, which is part of the NEP, on not only the Malays, but also the Chinese, who continue to dominate in this field despite being a minority.
Includes bibliographical references : (page 163-185) and index.
Keywords: Entrepreneurship -- Malaysia; Malays -- Economic conditions